Review of the 1977 Decision on Surveillance over Exchange Rate Policies : Proposal for a New Decision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper presents a draft Decision that reflects the guidance provided by the Board. In February, the Board endorsed three overarching principles to guide a new Decision: (i) no new obligations for members, together with confirmation that dialogue and persuasion are key pillars of surveillance; (ii) due regard for country circumstances and emphasis on the need for evenhandedness; and (iii) continued flexibility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet